2. „Mała Wielka Gra” – Kirgistan pomiędzy Federacją Rosyjską a USA w aspekcie militarnym .......... 311 - Torłop, Sebastian (Kirgistan – oblicza transformacji, 2020)
„THE SMALL GREAT GAME” – KYRGYZSTAN BETWEEN THE RUSSIAN FEDERATION AND THE US IN THE MILITARY ASPECTOriginally, the term “the Great Game” referred to the rivalry of two empires – the Russian and the British – for influence in Central Asia. The author tries to redefine this concept and give it a contemporary character. The text describes the competition for influence between the United States of America and the Russian Federation, which after the collapse of the USSR is trying to renew its power position in international relations. The author synthetically shows the changes taking place in Kyrgyzstan after independence, presents the genesis of the US military presence in this country, and also presents the “small Great Game” between the interested powers that are trying to base their sphere of influence on the military aspect.